Outcomes of Repeat Deep Anterior Lamellar Keratoplasty in Keratoconus: Case Series - Kirat O; Fairaq R; AlMutlak M; AlQahtani RS; AlHussein GA; AlHilali S (Clinical Ophthalmology)
Omar Kirat,1 Rafah Fairaq,1 Mohammed AlMutlak,1 Raneem S AlQahtani,2 Ghadah A AlHussein,2 Sara AlHilali1 1Anterior Segment Division, King Khaled Eye Specialist Hospital and Research Center, Riyadh, Saudi Arabia; 2Surgery Department, Aldiriyah Hospital - Riyadh Third Health Cluster, Riyadh, Saudi ArabiaCorrespondence: Sara AlHilali, Anterior Segment Division, King Khaled Eye Specialist Hospital and Research Center, Riyadh, Saudi Arabia, Tel +966544017155, Email SaraAlHilali@gmail.comPurpose: To report the incidence, indications, and clinical outcomes of repeat deep anterior lamellar keratoplasty (DALK) in keratoconus patients.Methods: Case series.Results: This retrospective study included all repeat DALK procedures for keratoconus performed at King Khaled Eye Specialist Hospital (KKESH) between 2016 and 2024. Patient demographics, surgical techniques, complications, and outcomes were analyzed. Among 2136 primary DALK procedures, only 0.66% (14 eyes) required repeat keratoplasty. The mean age at the time of repeat DALK was 32 and the mean follow-up duration was 30 months. Indications included lipid keratopathy (28.6%), persistent epithelial defect with severe immune reaction (14.3%), high irregular astigmatism (14.3%), and stromal scarring (7.1%). Graft exchange alone was sufficient in most cases (64%), while larger trephination and further dissection (22%) were performed for stromal scars or host rim ectasia. Postoperative complications (43%) included loose sutures (36%), elevated intraocular pressure (7%), and cataract formation (7%). The overall graft survival rate was 93%, with one failure due to poor compliance with postoperative steroids and follow-ups. Visual recovery was favorable, with 57% achieving 20/40 or better.Conclusion: Repeat DALK is a safe and effective alternative to penetrating keratoplasty (PK) for failed primary DALK, offering high graft survival and favorable visual outcomes while minimizing immune-related complications. Postoperative adherence and timely steroid management are critical for optimizing success. Further studies comparing repeat DALK and repeat PK are needed to assess long-term endothelial health and visual stability.Keywords: deep anterior lamellar keratoplasty, (DALK), keratoconus, repeat keratoplasty